PENGARUH STIGMA SOSIAL TERHADAP PENYANDANG DISABILITAS DI LEMBAGA PEMASYARAKATAN KELAS I SEMARANG - Naufal Tahtiar Rizqi; Mitro Subroto (Yustitia, 2025)
This study delves deep into the impact of social stigma experienced by individuals with disabilities serving their sentences at Semarang Class I Penitentiary. Employing a qualitative approach, this research involved in-depth interviews with various stakeholders, including inmates with disabilities, prison officers who interact directly with them, and other parties involved in the correctional system. The results demonstrate that the social stigma experienced by individuals with disabilities within the penitentiary is complex and significantly impacts their quality of life. They often encounter social isolation, feeling ostracized, and struggling to build healthy social relationships with other inmates and prison officers. Stigma can also lower their self-esteem and make them feel powerless. Consequently, the process of social rehabilitation, which should be the primary goal of correctional institutions, is hindered. Individuals with disabilities may find it difficult to participate in various correctional programs due to physical barriers or discrimination. The findings of this study highlight the importance of efforts to change societal perceptions, including those of prison officers, towards individuals with disabilities. A paradigm shift is needed, one that views individuals with disabilities as individuals with equal rights and equal potential to contribute to society. Additionally, efforts must be made to create an inclusive prison environment where all inmates, including those with disabilities, can live and function with dignity and without discrimination.